Embitterment societal, psychological, and clinical perspectives - Linden, Michael; Maercker, Andrea; SpringerLink (Online service).
Embitterment is a distinct state of mood known to everyone. It can be seen in the context of exceptional though normal negative life events. It is an emotional reaction e.g. to humiliation, to being severely disappointed by others, or to violations of basic values. Embitterment is accompanied by other emotions like feelings of hopelessness and helplessness, poor moods and a lack of drive, and aggression towards oneself and others. It can end in suicide or even murder-suicide and in a distinct pathological state known as Posttraumatic Embitterment Disorder (PTED). But despite the high prevalence rates, the detrimental effects on individuals and its forensic and societal importance, embitterment has yet to receive due scientific attention. In this book pioneers in embitterment research summarize the current knowledge on embitterment, it triggers, phenomenology and consequences. The work is intended to stimulate international debate and to contribute to a better understanding of embitterment and a deeper appreciation of the impact of exceptional but normal negative life events on psychological well-being
1. Psychology and neurobiology of embitterment -- PTSD and beyond. The embitterment reaction -- The psychology of embitterment -- Psychology of hope and despair -- The belief in a just word -- Personality and embitterment reactions -- Neurobiological Correlates of Social Exclusion and Social Pain -- Revenge -- Wisdom psychology -- 2. Context of embitterment -- Partnership and embitterment -- Bereavement and embitterment -- Life Span development, old age and embitterment -- Cancer and embitterment -- Work and Embitterment -- The Asian perspective on "loosing one?s face" -- War trauma, Displacement and Embitterment -- 3. Treatment of embitterment -- Pharmacotherapeutic options in the treatment of reactive disorders and embitterment Forgiveness theraps -- Wisdom psychotherapy -- 4. Legal, societal, and political dimensions of embitterment and forgiveness -- Homicide-suicide and forensic aspects of injustice, humiliation and embitterment -- Introduction: Embitterment and the German Reunification -- Forgiveness education in Northern Ireland -- Embitterment and Apartheid -- 5. Embitterment and the classification of mental disorders -- The differentiation between normal and pathological emotion. Should embitterment be listed in glossaries of psychopathological terms -- Differentiation between "Reactive mental disorders" and adjustment problems because of personality (-disorders) -- Classification of reactive mental disorders in ICD and DSM -- Context factors and reactive disorders in the Posttraumatic Embitterment Disorder.
Electronic reproduction.
Keywords: Adjustment disorders; Post-traumatic stress disorder; Electronic books